2009
DOI: 10.1016/j.amjmed.2008.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Long-term C-Reactive Protein Variability and Prediction of Metabolic Risk

Abstract: Purpose-This analysis was undertaken to determine the long-term intraindividual variability, determinants of change, and capacity of the inflammatory marker, C-reactive protein (CRP), to predict metabolic traits and diabetes in a large community-based population.Methods-Intraindividual CRP variability, predictors of CRP change and metabolic events were evaluated in the Framingham Heart Study Offspring cohort using data from the same 2409 participants with CRP measured by the same methodology at each of 3 exam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
4
22
1
Order By: Relevance
“…The authors of the last study [16] explained higher hsCRP levels by a higher percentage of adipose tissue in women than in men. It is possible that the similar hsCRP levels observed by our research team and found previously by other authors [18,19] reflect either smaller differences in fat content between men and women participating in these studies or may result from higher levels of proinflammatory cytokines stimulating systemic low-grade inflammation. Such a role may be played by TNF-a, and possibly also by interleukin-6, being the most important stimulator of CRP production [20].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The authors of the last study [16] explained higher hsCRP levels by a higher percentage of adipose tissue in women than in men. It is possible that the similar hsCRP levels observed by our research team and found previously by other authors [18,19] reflect either smaller differences in fat content between men and women participating in these studies or may result from higher levels of proinflammatory cytokines stimulating systemic low-grade inflammation. Such a role may be played by TNF-a, and possibly also by interleukin-6, being the most important stimulator of CRP production [20].…”
Section: Discussionsupporting
confidence: 51%
“…Studies conducted hitherto have provided conflicting results; the obtained results are in line with the findings of some [18,19] but not other [16] research groups. The authors of the last study [16] explained higher hsCRP levels by a higher percentage of adipose tissue in women than in men.…”
Section: Discussioncontrasting
confidence: 35%
“…Between two routine examinations (a mean of 16 years apart), approximately half of the more than 2,000 individuals studied remained within the same quintile of CRP values. 32 …”
Section: Specific Biomarkersmentioning
confidence: 99%
“…Prior studies have reported the relations of CVD risk factors to circulating inflammatory biomarkers assessed on a single occasion [57]. Nevertheless, there are only a few observational studies available examining the longitudinal progression of circulating inflammatory biomarkers [8]. Understanding modulators of longitudinal progression in inflammation potentially may improve early recognition of atherosclerosis and enhance risk prediction of CVD beyond traditional clinical risk factors [4].…”
Section: Introductionmentioning
confidence: 99%